Pengembangan metode pembelajaran Quantum Teaching mata pelajaran Bahasa Arab kelas V pada MI Nurul Huda I Miji dan MI Nurul Huda 2 Surodinawan Kota Mojokerto. - Muhammad Andi Isya' (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Over time, education experts have successfully created a new formula had appalling education. Bobby DePorter one education expert has created a new and practical way to affect the mental state of students conducted by the teacher. All were summarized in Quantum Teaching, which means the conversion of a variety of interactions that exist within the students into something beneficial for both the students themselves and for others. The purpose of this development study is: it produces the product of the teaching methods that are implemented Quantum Teaching Skills Approach process consisting of manual teaching methods Quantum Teaching. Products Quantum Teaching learning method has been refined based on the analysis of trial data. Based on the measures that have been implemented can be concluded as follows. 1). Products are revised based on test results of theoretical and empirical are: assessment experts do not indicate a revision, but the results of the questionnaire, the revision by the student based on the questionnaire: (1) Changing procedure of evaluation in the use of the model (2) Fix the model view or change strategy learning. 2.) The products developed interesting for classical learning in the classroom and independently. 3) The product of these products can ease the burden of teachers in teaching. 4) The results of expert validation and testing, Quantum Learning methods Teaching to develop critical thinking skills is fit for use for learning .5) products developed can increase students' motivation, and motivation is one of the conditions of implementation of productive learning model in the form method Quantum teaching learning to develop critical thinking skills.